Epidemiologia molecular de surtos de Adenite equina no Rio Grande do Sul - Brasil - Libardoni, Felipe (2012)
Strangles is an equine infectious disease that affects the upper respiratory tract, being considered the main respiratory disease in horses. The etiologic agent is Streptococcus equi subsp. equi (S. equi), responsible for approximately 30% of horse diseases worldwide notifications. The clinical signs of strangles are fever, nasal secretion and lymph node enlargement. The last one occurs due the incomplete phagocytosis of S. equi by defense cells because the presence of hyaluronic acid capsule and M protein (SeM) on the bacteria. The understanding of strangles epidemiology and its control is still limited. Molecular studies demonstrate differences in the gene sequence that codify the N-terminal region of the M protein (SeM) of S. equi. This gene region was already used in the differentiation of isolates by characterization of different alleles. This thesis aims to analyze and differentiate 47 S. equi isolates from equine clinical specimens from southern Brazil (15 Thoroughbred horses, 29 animals from the Crioula breed and three Brasileiro de Hipismo) through phylogenetic analysis and differentiation of alleles based on sequencing of the N-terminal region of the SeM protein. Samples were obtained from 31 outbreaks in 20 premises. Fifteen alleles were identified being only one (allele 9), with 7 isolates (14.9%), was already available in the PubMLST-SeM database (allele 61). Among the new identified alleles, the number 1 was the most prevalent with 13 isolates (27.7%), followed by allele 3 with 10 isolates (21.3%). The results demonstrate the great diversity of the amino acid sequence among the S. equi isolates from the studied equine population. Therefore the N-terminal sequence of SeM gene of the S. equi isolates is a useful tool in epidemiological investigation to differentiate isolates in strangles outbreaks with the identification of alleles in horses population, and may represent an alternative for to control the illness with guidance in selecting strains for production of commercial and autogenous vaccines.